Masculinities, History and Cultural Space: Queer Emancipative Thought in Jamie O’Neill’s At Swim, Two Boys - Milewski, Jarosław (Text Matters: A Journal of Literature, Theory and Culture, 2018)
At Swim, Two Boys, a 2001 novel by Jamie O’Neill, tells a story of gay teen romance in the wake of the Easter Rising. This paper considers the ways in which the characters engage in patterns of masculine behaviour in a context that excludes queer men, and the rhetorical effect of transgressive strategies to form a coherent identity. These patterns include involvement with the masculine and heteronormative nationalist movement, as well as a regime of physical exercise, and a religious upbringing in 20th-century Ireland. The strategies of broadening the practices of masculinity include their renegotiation and redefinition, as well as attempts to (re)construct the Irish and the gay canons of history and literature. These strategies, as exemplified by character development, become a rhetorical basis for the novel’s main argument for inclusiveness. This analysis deals with the central metaphors of space and continuity in the novel in the light of a struggle between identities. It also observes the tradition of parallels drawn between the emasculated position of the gay man and the Irish man at the beginning of the 20th century, and O’Neill’s rhetorical deployment of the shared telos in construction of a coherent gay Irish revolutionary identity.